Response and Tolerance Mechanism of Cotton Gossypium hirsutum L. to Elevated Temperature Stress: A Review - Zahid, Kashif Rafiq; Ali, Farhan; Shah, Farooq; Younas, Muhammad; Shah, Tariq; Shahwar, Durri; Hassan, Waseem; Ahmad, Zahoor; Qi, Chao; Lu, Yanli; Iqbal, Amjad; Wu, Wei (Frontiers in Plant Science, 2016)
Cotton is an important multipurpose crop which is highly sensitive to both biotic and abiotic stresses. Proper management of this cash crop requires systematic understanding of various environmental conditions that are vital to yield and quality. High temperature stress can severely affect the viability of pollens and anther indehiscence, which leads to significant yield losses. Cotton can respond to withstand adverse environmental condition in several phases among which the accumulation of chemicals is extremely vital. Calcium, kinases, reactive oxygen species, carbohydrate, transcription factors, gene expression regulation, and plant hormones signaling pathways are playing a handy role in activating the major genes responsible to encounter and defend elevated temperature stress. The production of heat shock proteins is up-regulated when crops are unleashed to high temperature stress. Molecular breeding can play a functional role to identify superior genes for all the important attributes as well as provide breeder ready markers for developing ideotypes. The development of high-temperature resistant transgenic cultivars of cotton can grant a stability benefit and can also ameliorate the production capacity in response to elevated temperature.